2020
DOI: 10.5114/ceji.2020.94702
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of polymorphism rs2230054 in CXCR2 gene with gout in Chinese Han male population

Abstract: neutrophils are crucial in the process of gout flare and remission. The signal transduction pathway of chemokine plays a vital role in the chemotaxis and activation of neutrophils. CXCR2 gene knocked out can avoid the acute neutrophilic inflammation stimulated by monosodium urate (MSu) crystals in mice. To investigate the relationship among CXCR1 rs2234671, CXCR2 rs1126579, and rs2230054 polymorphisms with gout arthritis flare in the Chinese han male population, a case-control study was carried out in 412 gout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Chemokines are mainly responsible for the recruitment and movement of cells and involved in the proceeding of atherosclerosis 29 . Meanwhile, chemokines play vital roles in the process of gout flare and remission 30 .Therefore, the activation chemokines signaling pathway may contribute simultaneously to atherosclerosis and gout. Regulation of actin cytoskeleton is also found to be activated.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines are mainly responsible for the recruitment and movement of cells and involved in the proceeding of atherosclerosis 29 . Meanwhile, chemokines play vital roles in the process of gout flare and remission 30 .Therefore, the activation chemokines signaling pathway may contribute simultaneously to atherosclerosis and gout. Regulation of actin cytoskeleton is also found to be activated.…”
Section: Discussionmentioning
confidence: 99%
“…The body’s immune system identifies MSU crystals as foreign invaders, triggering the innate immune response and leading to inflammation through signal transmission. , These crystals, which are endogenous danger signals, are detected by pattern-recognition receptors (PRRs), including both intracellular receptors (NLRs) and membrane receptors (TLRs). Recognition of MSU crystals can activate TLRs and the NALP3 inflammasome signal transduction, which controls the secretion of IL1β.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the CXCR1 gene rs2234671 and CXCR2 gene rs1126579 in the gouty arthritis group were not related to the susceptibility of gout in Chinese men. The CXCR2 gene rs2230054 is related to the susceptibility of gout in Chinese men ( 28 ). Research by Ying Ye et al.…”
Section: Discussionmentioning
confidence: 99%